How Does Inclusive Leadership Curb Workers’ Emotional Exhaustion? The Mediation of Caring Ethical Climate and Psychological Safety - Li, Xintian; Peng, Peng (Frontiers in Psychology, 2022)
The COVID-19 pandemic has transformed the politics, economy, and society of the world, which has dealt the most severe blow to the hospitality industry. Meanwhile, the pandemic and government control policies have brought high psychological pressure to hospitality front-line employees, resulting in emotional exhaustion. As a part of burnout syndrome, emotional exhaustion poses a threat to employees’ mental health, career sustainability, and well-being. Therefore, the purpose of this paper was to investigate the curb effectiveness of inclusive leadership on emotional exhaustion and to explore the mediation roles of ethical climate and psychological safety between them. Time-lagged data were collected from 65 teams and 358 hospitality front-line employees working in Chinese hotels in two stages with a one-month gap. This research verified that inclusive leadership has a negative impact on emotional exhaustion both indirectly through the mediation roles of ethical climate and psychological safety. And the ethical climate and psychological safety played partial mediation roles between inclusive leadership and emotional exhaustion. In theory, the findings explored the dual mediation mechanism of the inhibitory effect of inclusive leadership on emotional exhaustion. In practice, we provided the training and correct guidance to develop inclusive leadership for hotel enterprises and to resolve the emotional exhaustion of employees, which can enhance sustainability in careers.